2012
DOI: 10.1111/j.1365-2966.2012.20490.x
|View full text |Cite
|
Sign up to set email alerts
|

Galaxy properties from the ultraviolet to the far-infrared: Λ cold dark matter models confront observations

Abstract: We combine a semi-analytic model of galaxy formation with simple analytic recipes describing the absorption and re-emission of starlight by dust in the interstellar medium of galaxies. We use the resulting models to predict galaxy counts and luminosity functions from the far-ultraviolet (FUV) to the submillimetre, from redshift five to the present, and compare with an extensive compilation of observations. We find that in order to reproduce the rest-UV and optical luminosity functions at high redshift, we must… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
276
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 239 publications
(291 citation statements)
references
References 173 publications
(285 reference statements)
15
276
0
Order By: Relevance
“…In other words, galaxies at a comparable luminosity at highredshift compared to a local analog needed less dust obscuration. This made reproducing the observed properties of dusty galaxies at high-z more difficult, however, and as a consequence the Somerville et al (2012) model was unable to match the observed 250 µm SPIRE number counts, as well as the 850 µm Scuba counts. As shown by Niemi et al (2012), the Somerville et al (2012) model works rather well at lower redshifts (i.e.…”
Section: Semi-analytic Methodsmentioning
confidence: 97%
See 3 more Smart Citations
“…In other words, galaxies at a comparable luminosity at highredshift compared to a local analog needed less dust obscuration. This made reproducing the observed properties of dusty galaxies at high-z more difficult, however, and as a consequence the Somerville et al (2012) model was unable to match the observed 250 µm SPIRE number counts, as well as the 850 µm Scuba counts. As shown by Niemi et al (2012), the Somerville et al (2012) model works rather well at lower redshifts (i.e.…”
Section: Semi-analytic Methodsmentioning
confidence: 97%
“…It is noted, however, that this model over produces stars in massive galaxies, and therefore is incompatible with observations of local galaxies. Somerville et al (2012) presented an updated form of the Somerville & Primack (1999) SAM (i.e. the "Santa Cruz SAM") that was combined with estimates for dust attenuation by both diffuse dust and stellar birth clouds surrounding young clusters.…”
Section: Semi-analytic Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…• Popping et al (2014, SAM): Popping et al implemented pressure-based (Blitz & Rosolowsky 2006) and the metallicity-based (Gnedin et al 2009) H2 formation models in the Santa Cruz semi-analytical model (Somerville & Primack 1999;Somerville et al 2008aSomerville et al , 2012, in which the dark matter halo merger tree was constructed using the Extended Press-Schechter formalism ( star formation from molecular gas , and feedbacks from SNe and AGN. We obtain their MH 2 /M⋆ values (metallicity-based H2 model and star formation model based on Bigiel et al 2008) from Fig.…”
Section: Galaxy Formation Models In the Literaturesmentioning
confidence: 99%